Implementasi Penggunaan Layanan Pengadaan Secara Elektronik (LPSE) Terhadap Proses Pengadaan Barang Dan Jasa Di PT Xyz - Mitha Anggisna Angreini; R. Yuniardi Rusdianto (International Forum of Researchers and Lecturers, 2024)
This study explores the implementation of Electronic Procurement Service (LPSE) and its impact on the procurement processes for goods and services. The research focuses on understanding how the adoption of LPSE influences efficiency, transparency, and accountability in the procurement activities of organizations. Through a comprehensive analysis, the study evaluates the integration of LPSE in streamlining the procurement workflow, reducing manual intervention, and enhancing communication between stakeholders. The findings highlight the advantages and challenges associated with the electronic procurement system, shedding light on potential improvements for optimal utilization. The study contributes to the broader discourse on digital transformation in procurement, emphasizing the need for organizations to adapt and leverage technology to enhance overall procurement effectiveness.